Chemical Composition and Biological Activities of the Essential Oils of Leptospermum petersonii and Eucalyptus gunnii - Caputo, Lucia; Smeriglio, Antonella; Trombetta, Domenico; Cornara, Laura; Trevena, Greg; Valussi, Marco; Fratianni, Florinda; De Feo, Vincenzo; Nazzaro, Filomena (Frontiers in Microbiology, 2020)
The aim of this study was to characterize the chemical composition and to evaluate the antimicrobial and phytotoxic properties of the essential oils (EOs) obtained from leaves of Leptospermum petersonii chemotype “Variety B” and Eucalyptus gunnii, native to Australia. Geranyl acetate, γ-terpinene, geraniol, terpinolene, α-pinene, p-cimene, and linalool were the main components in L. petersonii EO, confirming also the existence of several chemotypes in such taxa; on the other hand, 1,8-cineole, trans-sabinene hydrate acetate, globulol, longicyclene, terpinolene, and camphene were present in major amounts in the E. gunnii EO. Chemical analysis of L. petersonii revealed that it belongs to the variety “B.” E. gunnii EO showed good antibacterial activity, with an MIC of 0.5 and 2 μg/mL against Staphylococcus aureus, and Pectobacterium carotovorum, respectively. The activity of E. gunnii EO was stronger than L. petersonii EO, whose maximum MIC reached 5 μg/mL. E. gunnii and L. petersonii EOs were particularly effective in inhibiting the biofilm formation by S. aureus, already at a concentration of 0.01 μg/mL. The other strains were resistant to both EOs up to a dose of 0.05 μg/mL. The maximum inhibition on biofilm formed by P. carotovorum was recorded for E. gunnii EO, reaching a value of 93.12% at 1.0 μg/mL. This is the first manuscript which studies the biofilm inhibition by EOs and evaluates their effects on biofilm metabolism. Both EOs were more effective against P. carotovorum. In addition, even though L. petersonii EO 0.1 μg/mL was unable to inhibit biofilm formation by Escherichia coli, it decreased the metabolic activity of the biofilm to 78.55% compared to control; furthermore, despite it inducing a relatively low inhibition (66.67%) on biofilm formation, it markedly affected metabolic activity, which decreased to 16.09% with respect to the control. On the contrary, L. petersonii EO 0.5 μg/mL induced a 79.88% inhibition of S. aureus biofilm, maintaining a high metabolic activity (90.89%) compared to the control. Moreover, this EO showed inhibitory activity against radical elongation of Solanum lycopersicum and the germination of radish. On the contrary, E. gunnii EO showed no phytotoxic activity.